An improved method for quantitative risk assessment of unconfined offshore installations subjected to gas explosions. (June 2020) - Xu, Yuxin; Bai, Yong; Paik, Jeom Kee; Dai, Weishun
Abstract: Previous related research has focused on consequences analysis of confined rather than unconfined structures against explosion accidents. This paper introduces an improved method for quantitative risk assessment of unconfined offshore installations subjected to gas explosions. In the present study, a floating, production, storage, and offloading unit (FPSO) is given as an example to present the proposed method. Instead of the most unfavorable scenario, lots of random scenarios are selected by the probabilistic sampling approach. The method for determining the equivalent gas cloud position is illustrated in the conversion between dispersion and explosion scenarios. Maximum and average overpressures are obtained by computational fluid dynamics (CFD) simulation. Besides overpressure exceedance curves, the combination of overpressure and probability method is adopted based on the definition of risk. This work allows finer scenarios' sampling results and reduces the computational costs.